The 'gizu': Winter grazing in South Libyan desert - Wilson, R.T. (1978)
Review of the published and unpublished literature on 'gizu', with particular reference to environment, calendar of occurence, flora composition, plant ecology, sociological aspects & economic aspects of the regional pastoral economy.